2019
DOI: 10.1080/24750573.2019.1693727
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and emotion regulation may be impaired in adolescents with obesity independent of the presence of binge eating disorder: a two-center study

Abstract: Background: Binge eating disorder (BED) and obesity in adolescents is associated with variations in social cognition and emotion regulation. The current study aimed to evaluate the Theory of Mind (ToM) abilities in adolescents with obesity with and without BED and to examine how they related to emotional and psychopathologic evaluations. Methods: One hundred twenty-eight adolescents comprising 32 non-BED adolescents with obesity, 32 adolescents with BED and obesity, and 64 healthy controls (HC) completed a bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…We identified six studies with similar task structures to explore emotion recognition. Four studies reported that obese subjects present difficulties in recognizing emotions based on general recognition accuracy, global errors, and rate of correct responses ( Baldaro et al, 1996 ; Koch and Pollatos, 2015 ; Percinel et al, 2018 ; Turan et al, 2019 ). Of these studies, one reported more errors in the recognition of specific emotions such as happiness and neutral expressions ( Baldaro et al, 1996 ).…”
Section: Concluding Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified six studies with similar task structures to explore emotion recognition. Four studies reported that obese subjects present difficulties in recognizing emotions based on general recognition accuracy, global errors, and rate of correct responses ( Baldaro et al, 1996 ; Koch and Pollatos, 2015 ; Percinel et al, 2018 ; Turan et al, 2019 ). Of these studies, one reported more errors in the recognition of specific emotions such as happiness and neutral expressions ( Baldaro et al, 1996 ).…”
Section: Concluding Considerationsmentioning
confidence: 99%
“…Similar difficulties in recognizing emotions in obesity were reported by Percinel et al (2018) in another study carried out in male and female obese adolescents compared to a normal weight group (refer to Table 1 ). Turan et al (2019) compared the global accuracy in an emotion recognition task between three groups of adolescents: (1) obesity plus binge eating disorder (BED) group; (2) obesity without BED group; and (3) normal weight group. The authors reported lower global emotion recognition accuracy in both obesity groups compared to the normal weight group (refer to Table 1 ).…”
Section: Introductionmentioning
confidence: 99%